2000
DOI: 10.1523/jneurosci.20-12-04555.2000
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heroin Self-Administration Desensitizes μ Opioid Receptor-Activated G-Proteins in Specific Regions of Rat Brain

Abstract: In previous studies from our laboratory, chronic noncontingent morphine administration decreased μ opioid receptor-activated G-proteins in specific brainstem nuclei. In the present study, μ opioid receptor binding and receptor-activated G-proteins were examined after chronic heroin self-administration. Rats were trained to self-administer intravenous heroin for up to 39 d, achieving heroin intake up to 366 mg · kg−1 · d−1. μ opioid-stimulated [35S]GTPγS and [3H]naloxone autoradiography were performed in adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
106
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 40 publications
14
106
6
Order By: Relevance
“…In the amygdala, it is not clear whether there is a direct interaction between AVP-producing cells and MOP-r activity. Despite an increased MOP-r binding density, earlier studies have found a decrease in MOP-r-stimulated G-protein (as reflected by GTPgS binding) in the rat amygdala after chronic heroin self-administration (Sim-Selley et al, 2000;Kruzich et al, 2003), suggesting involvement of amygdalar MOP-r desensitization in heroin dependence. Our recent finding that cocaine withdrawal stress increases the AVP mRNA in the amygdala through opioid receptors, suggests a functional interaction between the opioidergic and AVPergic systems in the amygdala (Zhou et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…In the amygdala, it is not clear whether there is a direct interaction between AVP-producing cells and MOP-r activity. Despite an increased MOP-r binding density, earlier studies have found a decrease in MOP-r-stimulated G-protein (as reflected by GTPgS binding) in the rat amygdala after chronic heroin self-administration (Sim-Selley et al, 2000;Kruzich et al, 2003), suggesting involvement of amygdalar MOP-r desensitization in heroin dependence. Our recent finding that cocaine withdrawal stress increases the AVP mRNA in the amygdala through opioid receptors, suggests a functional interaction between the opioidergic and AVPergic systems in the amygdala (Zhou et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…(Table 1). Adult rats treated chronically with morphine or heroin resulted in μ receptor desensitization in the thalamus, periaqueductal gray, and brain stem [12,21,23]. One major difference with the previous studies was that desensitization in adults occurred after 12 days of morphine infusion and 34 to 40 days of heroin self-administration.…”
Section: Behavioral Expression Of Morphine Tolerance In P17 Ratsmentioning
confidence: 84%
“…]GTPgS autoradiography is a method that allows visualization and quantification of functional G-proteincoupled receptors in brain slices (Sim et al, 1997a). This method has been used, for example, to demonstrate changes in m-opioid receptor function after chronic morphine and heroin treatments (Sim et al, 1996b;Sim-Selley et al, 2000), decreases in cannabinoid receptor activation after repeated tetrahydrocannabinol (Sim et al, 1996a), and heterologous regulation of 5-HT 1A receptors (Valdez et al, 2002). In the current study, autoradiography of LSD-stimulated [ 35 S]GTPgS binding revealed a region-specific attenuation of the cell signaling capacity of 5-HT 2A receptors in rats chronically treated with LSD.…”
Section: Discussionmentioning
confidence: 99%